(3TQM GdaUhd GdfUQjIs - (3GdMSjfj, GdGSJQGHGPj, YHO GdhgGH Hf Ydj, J JbQjHG (B875(3g`s ((3GdMSjf Hf eMeO GdNWjs)
(3ChdgG (B:s
(3fMeOc Gddge Ydi eG habJfG (B... (3CeG HYO(B... (3GdhGLH Ydi cd YGbd GdGTJZGd HGdGSe heG jchf GdaGFOI ajg(B..s
(3BNQgG (B:s
(3bhdg(B: (3hCeG GdPjf TbhG aaj GdfGQ dge ajgG RajQ hTgjb (B... (3hdfNJe GdcdGe MGeOjf(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B343s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B640s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds